Community Engagement: A Critical Guide for Practitioners: Chapter 9: Critical Discourse Analysis (Concept: The Journal of Contemporary Community Education Practice Theory, 2018)
Anne O’Donnell introduces Chapter 9 of 'Community Engagement: A Critical Guide for Practitioners'